The Effect of Independence and Red Flags on Fraud Detection Skills Through Professional Scepticism - Rubiyanty, Inggrid Marisca; Restianto, Yanuar Eko; Rokhayati, Hijroh (Juara: Jurnal Riset Akuntansi, 2024)
In recent years, corruption cases have continued to increase and involve high-ranking officials and lower officials both within the central government and local governments. Failure to detect fraud or fraud detection skills is one of the causes of the high rate of corruption. The purpose of this study was to determine and analyze the relationship between independence and red flags on the ability to detect fraud with professional skepticism as an intervening variable. This study uses a quantitative approach with 59 respondents from the Regency and City Government Internal Supervisory Apparatus (APIP) obtained through snowball sampling. Structural equation modeling (SEM) is used as a data analysis technique. The results showed that, independence affects fraud detection skills but has no effect on professional skepticism, red flags have no effect on fraud detection skills but affect professional skepticism and skepticism affects fraud detection skills. This study also examines the indirect relationship of variables with the results showing that independence has no effect on fraud detection skills mediated by professional skepticism and red flags have no effect on fraud detection skills mediated by professional skepticism.